Implementation of Lean Methodology on the Main Assembly Line of an Automotive Plant to Enhance Productivity - Amber Iqbal; M. Nasir Bashir; Asna Alam; M. Bilal Asif; Iqra Arshad (Journal of ICT, Design, Engineering and Technological Science, 2020)
Productivity can be enhanced by reducing wastages in a process while maintaining or increasing the amount of output. This is real work carried out in the automotive industry. In our work, we enhanced the productivity of the assembly line in an automotive plant by applying lean methodologies. There is an extensive range of tools available to remove all kinds of wastes, from which we selected the following two tools to remove waste that will enhance productivity, Value Stream Map (VSM) and Overall Equipment Effectiveness (OEE). The purpose of using VSM is that it easily highlights the bottlenecks in any existing process. For VSM we need to conduct a time and motion study to understand the structure of an organization. At the same time, OEE helps us measure the efficiency of our system being utilized. After applying these tools, we easily identified the parts which needed improvement in the process. It has reduced our cycle time of sub-assemblies by 50% and transportation time by 60%. This overall enhanced the productivity of the system by 20%. The index of OEE increased by 2%. Our work has improved the productivity of the assembly line in an automotive plant. In the future this work can be further improved by our successors for better productivity, fulfilling future customer needs.